Clinical Perspective on Thyroid Hormones and Autoantibodies in Subclinical Hypothyroidism (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
This study examines biochemical and immunological markers in individuals with subclinical hypothyroidism (SCH), particularly focusing on thyroid autoantibodies' role in disease progression. We recruited 200 patients from Vinayaka Mission Medical College and Research Institute having normal levels of triiodothyronine (T3) and tetraiodothyronine (T4) and excessive levels of thyroid stimulating hormone (TSH) (>4.0 mIU/L). Overt hypothyroidism, pregnancy, thyroid medication, and other illnesses that affect thyroid function were among the exclusion criteria. Chemiluminescent immunoassay and the Enzyme Linked Immunosorbent Assay were used to test fasting blood samples for serum TSH, T3, T4, Anti-Thyroglobulin Antibodies (AB-TG), and Anti-Thyroid Peroxidase Antibodies (AB-TPO). Thyroid compensation was indicated by aberrant T3 and T4 levels and markedly raised TSH levels (6.3 ± 0.16 mIU/L) in SCH patients. A strong association between TSH and AB-TPO levels (r = 0.45, p < 0.01) suggests an autoimmune involvement, as do elevated levels of AB-TG (170.97 ± 3.617 IU/mL) and AB-TPO (11.77 ± 0.313 IU/mL). These results emphasize the autoimmune aspect of SCH and imply that tracking thyroid autoantibodies may help with the course and treatment of the condition. Future research should explore gender-specific strategies in SCH diagnosis and clinical care.